Backpack weight and load distribution: kinetic assessment tools in schoolchildren - scope review - Castro, Maria (2022)
The backpack is the most used mean of transporting school supplies among children and young people, and the weight and distribution of the load, in its inside, is often variable. The adverse consequences, resulting from these parameters, have raised a growing concern on the part of the scientific community, parents and teachers. To identify the kinetic parameters used to verify the effects of weight and load position, inside the backpack, in school aged children and young people.